What If It Never Happened? Subjective Treatment Effects of a Negative Shock on Youth Labour Market Outcomes in Developing Countries - Marta Favara; Richard Freund; Marcello Perez-Alvarez (Institute of Labor Economics (IZA), 2023)
This paper examines the subjective treatment effects of a negative shock created by the COVID-19 pandemic on the labour market outcomes of young adults in India, Peru, and Vietnam. We leverage subjective counterfactual outcomes at the individual-level that were purposely collected from over 7,000 individuals to this aim. Our findings suggest that the shock denied employment opportunities and reduced earnings. On average, the pandemic reduced monthly earnings by 19.4% and employment levels by 17.5% in our three-country-sample. Country-specific magnitudes are lowest for India and highest for Vietnam. However, these average effects belie that a substantial proportion of individuals, particularly those from disadvantaged backgrounds, are pushed into employment by the pandemic. This frequently comes at the expense of their education, hinting at youth labour acting as a buffer against transitory shocks. According to our findings, the perceived effects of the pandemic on labour market outcomes carry important implications for young people's well-being and behaviour. Individuals who are denied employment display significantly higher rates of anxiety, lower rates of COVID-19 vaccination, and lower desired fertility.
Keywords: J21; J11; C21; C83; D84; 330; subjective treatment effects; labour market; COVID-19; youth; developing countries